Genealogi Pemikiran ‘Abdullah ibn Ṣāliḥ al-Fawzān dalam Nilai-Nilai Pendidikan Islam pada Hadis Jihad: Telaah Kitab Minḥat al-‘Allām - Maghza Rizaka; Sellyana Verawati; Ikmal Tahzibil Huda; Alda Nihayatul A’rifah; Fahrur Razi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research discusses the genealogy of 'Abdullāh ibn Ṣāliḥ al-Fawzān’s thought, an Islamic scholar who examines the book Minḥat al-‘Allām. In this context, a comparison with Ibn Ḥajar, who adheres to the Shafi'i madhhab, shows differences in approach. Although al-Fawzān comes from the Hanbali madhhab, he chooses strong opinions supported by scholars. The research method used is a qualitative approach, exploring the Islamic educational values and al-Fawzān's thoughts on jihad in Minḥat al-‘Allām. The steps of analyzing al-Fawzān's thought genealogy involve a multicausal approach, considering historical context, personal experience, and intellectual influence. 'Abdullāh ibn Ṣāliḥ al-Fawzān emphasizes the importance of interpreting the Quran and Sunnah and accepts ahadith as a source of Islamic law. In deducing laws, al-Fawzān uses the Hadith method by considering the texts of the Quran and Hadith, the opinions of the companions, and the use of analogy. Al-Fawzān's thoughts on jihad-related hadiths demonstrate a broad understanding, considering social and historical contexts. His genealogical analysis depicts the influence of formal education, academic environment, scientific methodology, the heritage of Islamic scholarship, social-political experience, and interaction with other scholars. Al-Fawzān's thought represents a synthesis of experience and education, forming a deep understanding of hadith in a modern context.